Análisis agroecológico y económico de la explotación comercial de palmito (Bactris gásipaes) en la zona noreste de Quevedo. - Vega Pozo, Doris Narcisa (2012)
This study was conducted in the districts of Buena Fe and Valencia, in August of palm producers, in order to determine the characteristics agroecological methods for marketing and product profitability. The 8 companies cultivated an area of 323 hectares. The study was conducted in four stages: the period 1996 - 2000, 2001 - 2005, 2006 - 2008, and from 2009 to 2011. In each period, expenditures and revenues obtained with these inputs and built the statements of income. In all periods yield was obtained. Ultimately the three companies that worked with the crop until 2011, withdrew to continue with it for the problems encountered in marketing